Correction: Predicting falls in older adults: an umbrella review of instruments assessing gait, balance, and functional mobility (BMC Geriatrics, (2022), 22, 1, (615), 10.1186/s12877-022-03271-5) - Beck Jepsen, D.; Robinson, K.; Ogliari, G.; Montero-Odasso, M.; Kamkar, N.; Ryg, J.; Freiberger, Ellen; Masud, T. (BMC Geriatrics, 2022)
After publication of this article [1], the authors reported that the given and family names of the last author were incorrectly structured: ‘Masud Tahir’ should read ‘T. Masud’. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2022-10-21